“Somos quem podemos ser”: Engenheiros do Hawaii - jovens, rock, sensibilidades e experiências urbanas (1985-2003) - Souza, Gisele da Silva (2018)
This dissertation investigates the work of Engenheiros do Hawaii and the emergence of the generation of young people in the 1980s, leading to a discussion on rock and issues involving the young at this time. The research was developed from songs and analysis of the covers of the 18 official discs of the group, in which we can observe various themes, among them the youth and the city. The analysis is organized in three moments. In the first one, he recovers the trajectory of rock, its arrival in Brazil and the formation of the rock generation of the 1980s, as well as marketing issues, cultural circularity and social and political criticism in the songs of Engenheiros do Hawaii observing the tensions experienced in the country during this period. Thereafter, discussions about the cities and the youth are incorporated, bringing representations such as the flâneur, dândi, nihilism, existentialism, experiences of urban violence representations such as the flâneur, dândi, nihilism, existentialism, experiences of urban violence generating fear, insecurity, solitude and anguish. Including also the existential yearnings of the young, their discouragement and the issue of consumption, either alcohol or drugs, attempts to face pain and regrets, forget loves and void relationships. Other issues addressed are the concerns about the expansion of technology, its physical and social impacts, hopelessness in the face of wars and violence